Pengaruh Brand Equity Terhadap Loyalitas Nasabah Menabung Tabungan Marhamah Mudharabah Pada PT. Bank Sumut Syariah Kantor Cabang Pembantu Stabat - Winanda, Apri; Fadhila Rahma, Tri Inda; Syahriza, Rahmi (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This study was conducted to determine the effect of brand equity on customer loyalty in saving marhamah mudaraba savings at PT. Bank Sumut Syariah KCP Stabat. The research method used in this study is a quantitative approach. The data collection technique used is the distribution of questionnaires. The analytical technique used in this study is validity, reliability, classical assumptions, multiple linear regression, and hypothesis testing using SPSS version 25. Brand Awareness has a significant and positive relationship with customer loyalty in saving marhamah mudharabah savings. So that if brand awareness increases, customer loyalty in saving marhamah mudaraba savings will increase, and vice versa. Brand Associations have a significant and positive effect on customer loyalty in saving marhamah mudaraba savings. So that if brand associations increase, customer loyalty in saving marhamah mudaraba savings will increase, and vice versa. Brand Loyalty has a significant and positive relationship with customer loyalty in saving marhamah mudaraba savings. So that if brand loyalty increases, customer loyalty in saving marhamah mudaraba savings will increase, and vice versa. Perceived Quality has a significant and positive relationship with customer loyalty in saving marhamah mudaraba savings. So that if perceived quality increases, customer loyalty in saving marhamah mudaraba savings will increase, and vice versa. Brand awareness, brand associations, brand loyalty, and perceived quality together or simultaneously have a significant effect on customer loyalty in saving marhamah mudaraba savings.